2001
DOI: 10.1136/adc.84.2.183
|View full text |Cite
|
Sign up to set email alerts
|

Short report: Bone density in asthmatic children treated with inhaled corticosteroids

Abstract: Volumetric trabecular bone mineral density of the lumbar spine (vTBMD) and distal radius (rTBMD) were measured in 20 prepubertal white asthmatic children treated with moderate to high doses of inhaled corticosteroids. The median standard deviation score for vTBMD (0.20, −0.56 to 2.09) and rTBMD (−0.04, −0.82 to 1.39) were within the normal range. (Arch Dis Child 2001;84:183-184)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0
1

Year Published

2001
2001
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(13 citation statements)
references
References 3 publications
1
11
0
1
Order By: Relevance
“…Our data suggest that BUD diminishes bone formation, both mineralization and collagen synthesis, at least transiently, even at a dose of 400 g/d, whereas FP seems to diminish only the later mineralization phase of bone formation, and only at 500 g/d doses. These results are consistent with the recent study of Reilly et al (28), who found that FP is less likely than BUD to affect trabecular bone mineral density. On the other hand, during CROM treatment, both markers of bone formation tended to increase, probably reflecting normal agedependent growth and increase in bone mass (29,30).…”
Section: Discussionsupporting
confidence: 93%
“…Our data suggest that BUD diminishes bone formation, both mineralization and collagen synthesis, at least transiently, even at a dose of 400 g/d, whereas FP seems to diminish only the later mineralization phase of bone formation, and only at 500 g/d doses. These results are consistent with the recent study of Reilly et al (28), who found that FP is less likely than BUD to affect trabecular bone mineral density. On the other hand, during CROM treatment, both markers of bone formation tended to increase, probably reflecting normal agedependent growth and increase in bone mass (29,30).…”
Section: Discussionsupporting
confidence: 93%
“…study of healthy skeletal development [1][2][3][4][5][6][7][8][9][10] and for the assessment of paediatric disorders associated with skeletal fragility [11][12][13][14][15][16][17][18][19][20][21]. pQCT is designed to measure peripheral skeletal sites such as the radius, tibia and femur.…”
mentioning
confidence: 99%
“…Os estudos longitudinais e transversais não revelaram efeitos indesejáveis na mineralização óssea 13 . Por outro lado, os efeitos secundários locais não podem ser desprezados, como a sensação de sede (22%), disfonia (11%), candidíase oral (11%) 14 , estes dois últimos podendo ser significativamente reduzidos com bochechos e/ou escovação dos dentes após a inalação.…”
Section: Efeitos Colateraisunclassified